2010
DOI: 10.1002/ijc.25672
|View full text |Cite
|
Sign up to set email alerts
|

A novel 19F agent for detection and quantification of human dendritic cells using magnetic resonance imaging

Abstract: Monitoring of cell therapeutics in vivo is of major importance to estimate its efficacy. Here, we present a novel intracellular label for 19F magnetic resonance imaging (MRI)‐based cell tracking, which allows for noninvasive, longitudinal cell tracking without the use of radioisotopes. A key advantage of 19F MRI is that it allows for absolute quantification of cell numbers directly from the MRI data. The 19F label was tested in primary human monocyte‐derived dendritic cells. These cells took up label effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 36 publications
4
59
0
Order By: Relevance
“…27 When PFCs were used for in vitro labeling experiments, no negative effects were found on cell viability and cell function of dendritic cells 28 and polymorphonuclear neutrophils. 29 In summary, these current and other preliminary results of 19 F MRI applications for inflammation detection and the fact that the PFCs exhibit a high safety profile, [27][28][29] suggest a feasible and highly desirable transition of this 19 F approach into a clinical application. From a biological point of view, future studies are needed to test whether human macrophages are able to incorporate PFC in vivo in sufficient quantities to allow for noninvasive detection by 19 F-CMR.…”
Section: Clinical Perspective: Applications In Humansmentioning
confidence: 99%
“…27 When PFCs were used for in vitro labeling experiments, no negative effects were found on cell viability and cell function of dendritic cells 28 and polymorphonuclear neutrophils. 29 In summary, these current and other preliminary results of 19 F MRI applications for inflammation detection and the fact that the PFCs exhibit a high safety profile, [27][28][29] suggest a feasible and highly desirable transition of this 19 F approach into a clinical application. From a biological point of view, future studies are needed to test whether human macrophages are able to incorporate PFC in vivo in sufficient quantities to allow for noninvasive detection by 19 F-CMR.…”
Section: Clinical Perspective: Applications In Humansmentioning
confidence: 99%
“…We, and others, have shown that the contrast generated by ironlabeled cells increases with the amount of iron/voxel but that this is only linear at low iron loadings; the change in contrast reaches a saturation plateau at higher iron loadings. 6,7 When quantifying the presence of iron-labeled stem cells over time, most studies measure the "signal void volume" 8,9 or the "number of black pixels", 10,11 and present the change relative to the first imaging time point.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 Other investigators have also reported on the ability to ex vivo label other potential cell therapies with 19 F, including murine 30 and human neural stem cells, 31 human CD34 C hematopoietic stem cells (HSCs) and mouse bone marrow derived HSCs as well as murine 32 and human 33 19 F-MRI without apparent toxicity. 34 About 10 million DCs were injected intradermally into quadriceps and patients were imaged for about 9.5 min.…”
mentioning
confidence: 99%